On the hydration of ions - Heinzinger, K.; Scha, H. (Condensed Matter Physics, 1999)
This report will concentrate on ions which are produced in nuclear power
reactors and/or which are of special interest because of their small radius
and/or their high charges, leading to hydrolysis. Mainly the results of Molecular Dynamics simulations will be discussed as they are able to provide a
comprehensive and consistent description of the structural and dynamical
properties of the water molecules in the hydration shells of the ions. Whenever reactions between the ions and the water molecules can occur, it will
be necessary to employ ab initio simulations such as the Car-Parinello
method. The difﬁculties connected with the investigation of uranium and
plutonium ions with this method are discussed. Дана доповідь зосереджена на іонах, які утворюються в ядерних реакторах і/або становлять особливий інтерес завдяки їхньому малому радіусу і/або їхнім великим зарядам, що приводить до гідролізу.
В основному будуть обговорені результати, отримані методом молекулярної динаміки, оскільки вони здатні забезпечити вичерпний і послідовний опис структурних і динамічних властивостей молекул води
в гідратаційних оболонках іонів. Які б реакції між іонами і молекулами
води не відбувалися, є необхідним застосовувати ab initio обчислення такі, як метод Кар-Парінелло. Обговорюються труднощі, пов’язані
з дослідженням цим методом іонів урану і плутонію.